2011
DOI: 10.1002/cm.20519
|View full text |Cite
|
Sign up to set email alerts
|

An axonemal PP2A B‐subunit is required for PP2A localization and flagellar motility

Abstract: Analysis of Chlamydomonas axonemes revealed that the protein phosphatase, PP2A, is localized to the outer doublet microtubules and is implicated in regulation of dynein-driven motility. We tested the hypothesis that PP2A is localized to the axoneme by a specialized, highly conserved 55-kDa B-type subunit identified in the Chlamydomonas flagellar proteome. The B-subunit gene is defective in the motility mutant pf4. Consistent with our hypothesis, both the B- and C-subunits of PP2A fail to assemble in pf4 axonem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 74 publications
(103 reference statements)
1
26
0
Order By: Relevance
“…A previous study using sequence similarity indicated that the Chlamydomonas genome contains four potential PP2A catalytic subunits, PP2A-1c (g4366), PP2A3 (g9684), PP2A-c4 (Cre12.g494900), and PPA1 (Cre06.g308350) [34]. Due to the sequence similarities observed among PP2A, PP4, and PP6 in all organisms [32], we asked whether the four Chlamydomonas proteins are PP2A catalytic subunits using phylogenetic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study using sequence similarity indicated that the Chlamydomonas genome contains four potential PP2A catalytic subunits, PP2A-1c (g4366), PP2A3 (g9684), PP2A-c4 (Cre12.g494900), and PPA1 (Cre06.g308350) [34]. Due to the sequence similarities observed among PP2A, PP4, and PP6 in all organisms [32], we asked whether the four Chlamydomonas proteins are PP2A catalytic subunits using phylogenetic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that different families of the B subunit target PP2A to different cellular locations and bind to different substrates [32], [33]. In Chlamydomonas , sequence similarity reveals four catalytic subunits, two scaffold subunits, and five regulatory subunits [34].…”
Section: Introductionmentioning
confidence: 99%
“…Since the C1d complex binds to CaM in high calcium, we also compared the effect of loss of FAP46 versus FAP74 on two Ca 2+ -mediated behaviors: phototaxis, in which cells swim toward or away from light; and photoshock, in which a sudden change in light intensity induces a momentary switching from the asymmetrical waveform used during forward swimming to the symmetrical waveform used during backward swimming, rapidly followed by a return to forward swimming (Bessen et al, 1980;Hyams and Borisy, 1978;Kamiya and Witman, 1984;Witman, 1993). Using a simple but sensitive photoaccumulation assay (Elam et al, 2011;King and Dutcher, 1997;VanderWaal et al, 2011), FAP74ami was found to be impaired in phototaxis as previously demonstrated using a more quantitative assay (DiPetrillo and Smith, 2011). Using the same simple assay, both fap46-1 and fap46-1xFAP74ami were severely impaired in the ability to phototax; only the FAP46-rescued strain exhibited WT phototaxis.…”
Section: C1d Assembly and Function 3907mentioning
confidence: 99%
“…Both the kinases and phosphatases responsible for this reversible modification (Howard et al , 1994; Yang et al , 2000; Yang and Sale, 2000) are integrated within the axonemal superstructure through specific anchoring proteins (Gaillard et al , 2001). These modifying enzymes (casein kinase and 1 and protein phosphatases 2A) directly control the rate of microtubule sliding powered by axonemal dyneins (Gokhale et al , 2009 ; Elam et al , 2011). Similarly, there is evidence that cAMP- and/or Ca 2+ -dependent phosphorylation of the p29 light chain within Paramecium outer arm dynein is directly linked to the control of motor output (Hamasaki et al , 1991; Barkalow et al , 1994).…”
Section: Key Dynein Regulatory Systemsmentioning
confidence: 99%